2014
DOI: 10.1021/op5000978
|View full text |Cite
|
Sign up to set email alerts
|

Process Development and Control with Recent New FBRM, PVM, and IR

Abstract: Process analytical technologies (PATs) have played an important role in process development and optimization throughout the pharmaceutical industry. Recent new PATs, including in-process video microscopy (PVM), a new generation of focused-beam reflectance measurement (FBRM), miniature process IR spectroscopy, and a flow IR sensor, have been evaluated, demonstrated, and utilized in the process development of many drug substances. First, PVM has filled a technical gap by providing the capability to study morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Such methods would also be applicable to the synthesis process itself [37]. In this study, the probe-based (fiber)optical technologies Photon Density Wave (PDW) spectroscopy [3841], Focused Beam Reflectance Measurement (FBRM) [4245], Particle Vision Microscope (PVM) measurement [4648], and turbidity measurement [49–51] are applied to study the LCST of aqueous PNIPAM suspensions and additionally its heating and cooling rate dependency.…”
Section: Introductionmentioning
confidence: 99%
“…Such methods would also be applicable to the synthesis process itself [37]. In this study, the probe-based (fiber)optical technologies Photon Density Wave (PDW) spectroscopy [3841], Focused Beam Reflectance Measurement (FBRM) [4245], Particle Vision Microscope (PVM) measurement [4648], and turbidity measurement [49–51] are applied to study the LCST of aqueous PNIPAM suspensions and additionally its heating and cooling rate dependency.…”
Section: Introductionmentioning
confidence: 99%
“…[18] This method is not recommended as it increased fouling in the bitumen system, which is thought to be due to more hydrocarbon material coating the window. Hommema [18] suggested that other treatments that are optically transparent may be suitable as well, such as TEFLON 1 . Treatments are best removed with physical polishing using a fine polishing paste.…”
Section: Resultsmentioning
confidence: 99%
“…F ocused beam reflectance measurement (FBRM) is a measurement technique that allows for in-situ dynamic measurements of particle or drop sizes in a process. The FBRM probe is used extensively in crystallization processes and a number of processes with a solid dispersed phase, [1][2][3][4][5][6][7] as well as in the study of liquid/liquid dispersions [7][8][9][10][11][12] and more recently it has been applied to crude oil systems. [13][14][15][16][17][18] The FBRM probe directs a laser beam through a sapphire window into the fluid and collects backscattered light.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleation and its mechanism are largely studied to get a further understanding of this key stage, mainly focusing on the qualitative and quantitative interactions between the solute, solvent, and external additives, and how the solute molecules self-assemble into different crystal forms, and what the exact mechanism and kinetics of nucleation is [3][4][5][6][7][8][9]. For growing crystals into the desired size and shape in the manufacturing process, a large portion of the literature is also reported to investigate the crystal growth process and its possible mechanisms [10][11][12][13][14][15]. Based on modeling and experimental techniques, many works are presently being performed on growth and shape control [10,12,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…FBRM can track the number of particles and chord length distribution in real-time, providing a quantitative calculation method for crystallization process modeling. The latest generation of FBRM overcomes the problem of probe contamination [11]. As a mature technology, Raman spectroscopy has been used to identify differences in polymorphisms, and it can perform qualitative and quantitative studies on solvent-mediated transformation, solution concentration, and the ratio of different crystal forms in solid mixtures [12].…”
Section: Introductionmentioning
confidence: 99%